On some Heteropoda species from Southeast Asia with new data on their biology and distribution range and the resurrection of a new species group (Sparassidae: Heteropodinae) - Jäger, Peter; Koh, Joseph K. H. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2024)
Eight species of the huntsman spider genus Heteropoda Latreille, 1804 are described; Heteropoda bufocorniculans spec. nov. (Sabah, Sarawak; female), H. sederhana spec. nov. (Java; female), H. temburong spec. nov. (Brunei, Sabah, Sarawak; male, female), H. trifurcata spec. nov. (Pahang State, Malaysia; male, female), H. tutula spec. nov. (Singapore; female), H. tympanum spec. nov. (Penang, Malaysia; female), H. ulna spec. nov. (Sumatra, Indonesia; female), and H. uniter spec. nov. (Kalimantan, Indonesia; female). The latter six species, along with H. ocyalina (Simon, 1887) and H. asa Jäger, 2024, are included in the newly proposed ocyalina species-group. H. fasciata (Reimoser, 1927) is removed from synonymy of H. ocyalina (Simon, 1887) and considered a nomen dubium. The male of Heteropoda borneensis (Thorell, 1890) is illustrated for the first time, male and female are redescribed, new distributional data are presented, including the first records from Brunei, Indonesia (Kalimantan Utara), Malaysia (Kuala Lumpur, Sabah), and Singapore. Heteropoda strandi Jäger, 2002 and H. lunula (Doleschall, 1857) are formally documented for the first time from Singapore, the female of the former is redescribed.